Development of freeze-dried products with frog meat for special diets: microbiological and sensory traits - de Lourdes Agostinho de Andrade, Maria (Revista Ciência Agronômica, 2021)
Frog meat has high nutritional value and can be used by children with food intolerances and by the elderly to prevent osteoporosis and arterial hypertension. In this study, we developed different instant-soup preparation methods using seasoned and shredded frog meat with vegetables ready for consumption after rehydration; as well as preparation methods for shredded, seasoned and dehydrated frog meat for use in the preparation of soups. Four preparation methods were considered in the sensory tests: M1 - Freeze-drying of the soup after preparation with seasoned frog back meat plus vegetables, M2 - Freeze-drying of the soup after preparation with seasoned frog leg meat plus vegetables; M3 - Soup prepared with freeze-dried seasoned frog back meat plus vegetables; and M4 - Soup prepared with freeze-dried seasoned frog leg meat plus vegetables. The freeze-dried powdered soups and the freeze-dried seasoned meats used in the preparation of the soups were subjected to the following microbiological analyses: count of thermotolerant coliforms and Bacillus cereus; identifi cation of coagulase-positive Staphylococcus; and isolation and identifi cation of Salmonella spp. The results of microbiological analyses showed that all samples met the standards established by the National Health Surveillance Agency of Brazil for frog meat, dried food fi sh and powder mixtures for instant products. The results of the acceptance test revealed that all soups were accepted in terms of overall impression and purchase intention, although M3 was statistically the least accepted (P < 0.05). The paired-comparison test did not indicate a preferred sample (P > 0.05). The availability of quality semi-prepared products will facilitate and expand frog meat consumption and marketing, promoting both the growth of the industry and the production sector and rendering frog farming more attractive and competitive.